THE LEISURE PRACTICES OF THE ACADEMICS OF THE VILA VELHA UNIVERSITY / UVV PHYSICAL EDUCATION COURSE IN THE FREE TIME (Fiep Bulletin - online, 2017)
The objective of this study is to identify the favorite recreational activities of physical education course academic at theUniversity Vila Velha / ES when they are in the free time of their academic and social obligations and opt for leisure. As well ascategorize these activities from cultural leisure interests. This descriptive and exploratory field research is based on directobservation of activities in the study group and semi-structured interviews. We conclude that the subjects interviewed in this study,from Monday to Friday trade after their academic and social obligations rather as leisure activities those that are restricted in virtualcultic and intellectual interests; leaving the sports physical and social interests in the background.